The relationship between dimension of perfectionism and emotion eegulation strategies in elite Taekwondo athletes - Sahar Zarei; Hassan Gharayagh Zandi; Nouri Nazaritaba; Mahmoud Mohebi (مجله علوم روانشناختی, 2018)
Perfectionism is a multi-dimensional trait which is effective on sports success. Although this factor is correlated with experiencing different emotions, its correlation with emotion regulation strategies is not considered. Therefore, the purpose of the present study was to investigate the the relationship between dimension of perfectionism and emotion regulation strategies in elite Taekwondo athletes. Present study research method was descriptive-correlational, Statistic population was included all of from Iranian Taekwondo athletes participating in super League competition. Samples were and 132 female and male selected based on random sampling, and completed the Scals of of perfectionism and emotion regulation. The data was analyzed by Pearson correlation and multiple regression (inward method) tests. The results revealed that positive perfectionism was positively associated with reappraisal strategies, and negatively correlated with negative suppression strategies. Negative perfectionism had the negative correlation with these strategies. Regression analysis showed that positive and negative perfectionism dimensions predict 33 and 41 percent of reappraisal and Suppression strategies variance respectively. According to the findings, we can conclude that dimensions of perfectionism have an important role in selecting emotion regulation strategies and the kind of strategies which every person uses is correlated with these dimensions.